Measurement of the cross section for top quark pair production in association with a W or Z boson in proton-proton collisions at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
A measurement is performed of the cross section of top quark pair production in association with a W or Z boson using proton-proton collisions at a center-of-mass energy of 13 TeV at the LHC. The data sample corresponds to an integrated luminosity of 35.9 fb−1 , collected by the CMS experiment in 2016. The measurement is performed in the same-sign dilepton, three- and four-lepton final states. The production cross sections are measured to be σ(t¯tW) = 0.77+0.12 −0.11(stat)+0.13 −0.12(syst) pb and σ(t¯tZ) = 0.99+0.09 −0.08(stat)+0.12 −0.10(syst) pb. The expected (observed) signal significance for the t¯tW production in same-sign dilepton channel is found to be 4.5 (5.3) standard deviations, while for the t¯tZ production in threeand four-lepton channels both the expected and the observed significances are found to be in excess of 5 standard deviations. The results are in agreement with the standard model predictions and are used to constrain the Wilson coefficients for eight dimension-six operators describing new interactions that would modify t¯tW and t¯tZ production.